A primary study on testing the electrical property of arc column in plasma arc welding. (June 2017) - Chen, Shujun; Zhang, Ruiying; Jiang, Fan; Li, Yuanfeng
Abstract: A welding arc is considered a composite of electron flow and electrically neutral arc plasma. Their interaction significantly affects the transmission and conversion process of the heat and momentum in welding process. Studying the electrical property of arc plasma is significant for understanding this interaction, but directly testing such property in arc column is still a challenge. In this paper, a novel method based on active probes was proposed/designed and used to test such a property in a welding arc plasma. The probes were partially coated to electrically insulate except for their tips. During test, the probes moved into the arc zone to detect the resistance between the tips. To minimize the damage to the probes, the movement of the probes was relatively quick such that the stay of the tips in the arc zone is minimal. In the meantime, electrical signals of the detection circuit and arc images were collected by a data acquisition system and a high-speed camera system. Images suggested that the movement of the probes imposed no noticeable effect on the behavior of the arc. On the other hand, the voltage to current ratio (V–I ratio) between the probe tips reduces as the moving speed of the tips reduces. Analysis suggests that the detection circuit is not purely resistive. As such, when the moving speed was reduced sufficiently, the V–I ratio approaches to a constant without changing with the moving speed. The effect from the dynamic property of the circuit on the measurement of the V–I ratio was thus eliminated. As such, the moving speed can be selected such that the dynamic behavior of the detection circuit becomes insignificant while the speed is still sufficient to minimize possible damage to the tips due to high temperature of the arc. Furthermore, the parameters of detection circuit were also discussed. As such, a novel method becomes available to study the electrical behavior of the arc plasma in the future study.